FRI0568-PC Gout: are we getting it right in primary care? an audit of serum uric acid level measurement and monitoring. (23rd January 2014) - Cooper, T.; Prouse, P. J.
Abstract : Background: Gout is a common and increasing cause of acute and chronic arthritis (1 ). Gout is responsible for a significant use of resources due to hospital admissions (2 ) for acute attacks. It is well known that lowering the serum uric acid level (SUA) can prevent attacks of gout. Allopurinol is the drug of choice for first line treatment after an initial gout attack. Modifying risk factors such as obesity and alcohol intake is another important aspect of management. EULAR and BSR have produced recommendations for the management of gout, namely keeping SUA <0.36mmol/L and annual measurement of SUA in treated patients (3, 4 ). Objectives: The objective was to examine the practice of gout treatment and monitoring in a general practice in the UK. We wanted to see whether the SUA level for all patients on allopurinol was measured annually and whether the levels reflected a treat to target approach of <0.36mmol/L. Methods: This study audited one general practice in the UK. Data were collected retrospectively for 3 years on all patients receiving allopurinol and having their SUA level measured via the practice computer database. Further information was recorded on whether the SUA was treated to target and whether it was measured annually. Results: A total of 125 patients had received allopurinol in the 3 year period. 76 patients (60.8%) had not had their SUA level measured, leaving only 49 (39.2%) who had their SUA levels checked. Of those who had their SUA levels measured only 6 patients (4.8%) had this done annually. Only 11 of the 125 patients (8.8%) had been treated to target (SUA <0.36mmol/L). Conclusions: Clearly the majority of patients receiving allopurinol in this general practice were not having their SUA levels measured, being treated to target or monitored annually. If these simple tests and management strategies were performed in primary care then a large number of hospital admissions for attacks of gout could be avoided, with the accompanying save in expenditure. It is planned to recall all patients receiving allopurinol for annual SUA level measurement and a treat to target approach. The study highlighted to all practice staff the importance of screening and monitoring SUA levels. References: Doherty M. New insights into the epidemiology of gout. Rheumatology 2009; 48(Supppl 2):2-8. HES online, Hospital admissions by diagnosis 3 code 2009-2012, available at http://www.hesonline.nhs.uk/Ease/servlet/ContentServer?siteID=1937&categoryID=203 (accessed 29 November 2012) Jordan KM, Cameron JS, Snaith M, et al. British Society for Rheumatology and British Health Professionals in Rheumatology Guideline for the Management of Gout. Rheumatology 2007; 46:1372-1374. Zhang W, Doherty M, Bardin T, et al. EULAR evidence based recommendations for gout Part II: Management. Report of a task force of the EULAR Standing Committee for international clinical studies including therapeutics (ESCISIT), Ann Rheum Dis; 2006; 65:1312-1324. Disclosure of Interest: None Declared